ANALISIS KRITIS PERAN KOMUNIKASI DAKWAH DALAM MENGURANGI ANGKA PERCERAIAN DI KABUPATEN ACEH TENGAH - Halihasimi, Halihasimi; Halihasimi, Halihasimi Halihasimi (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2022)
AbstractThe purpose of this study was to analyze the role of da'wah communication as a provider of information, as an educator and as a giver of advice. In addition, through the role of da'wah communication, it is hoped that it can reduce the divorce rate in Central Aceh Regency. This research uses descriptive qualitative method. Data collection techniques in this study used observation and interviews, as well as books, laws and regulations and journals related to the problem to be studied; Is the role of da'wah communication as a provider of information can reduce the divorce rate in Central Aceh District, Is the role of da'wah communication as an educator can reduce the divorce rate in Central Aceh District. Is the role of da'wah communication as an adviser to reduce the divorce rate in Central Aceh District. Conflicts in the household are managed in such a way with art and full of patience as motivation and strength to build the integrity of the household in the frame of divine guidance. Based on the analysis of the research results, it shows that the role of da'wah communication as a provider of information, as an educator and as a provider of advice can reduce the divorce rate in Central Aceh District. Families who do not take advantage of the role of da'wah communication will cause problems, miscommunication and often end in divorce.